Exploring socioeconomic inequalities in the use of medicinal herbs among Iranian households: evidence from a national cross-sectional survey - Satar Rezaei; Sina Ahmadi; Amjad Mohamadi-Bolbanabad; Ahmad Khanijahani (BMC, 2020)
Abstract Background Association between socioeconomic status and medicinal herbs (MH) are rarely documented in Iran. Our goal was to measure and decompose socioeconomic inequalities in MH use among Iranian households. Methods The data used in this cross-sectional study were extracted from the 2018 Household Income and Expenditure Survey (HIES) (N = 38,859). Data on MH use, age, gender, and education status of the head of household; a constructed wealth index of household (as a proxy for household's socioeconomic status); and place of residence (urban or rural) were obtained from the survey. Publicly available province-level data on Human Development Index (HDI) were obtained from the Institute for Management Research at Radbound University. We used the concentration curve and the normalized concentration index (C n ) to measure the magnitude of socioeconomic inequalities in MH among Iranian households. The C n was decomposed to identify the main determinants of socioeconomic inequalities in MH in Iran. Results The overall prevalence of MH use among Iranian households was 4.7% (95% confidence interval [CI]: 4.5 to 4.9%) in the last month before data collection. The C n for MH use for the whole of samples was 0.1519; 95% CI = 0.1254 to 0.1784; suggesting a higher concentration of MH use among the households with high socioeconomic level. The decomposition analysis indicated that the main contributing factors to the concentration of MH use were the economic status of households, development status of the province, and education level of the household head. Conclusions This study demonstrated that MH use is more concentrated among socioeconomically advantaged households in Iran and its provinces. This finding might contrast with the widespread belief that wealthy and socioeconomically advantaged populations, compared to low SES groups, tend to seek disproportionately more modern medical treatments and medications than MH. Understanding the factors affecting MH use, socioeconomic inequality in use of MH and its determinants provide an opportunity for health policymakers to design effective evidence-based interventions among providers and consumers of MH.